Dampak Kenaikan Harga Minyak Bumi terhadap Ketersediaan Minyak Goreng Sawit Domestik - Hartoyo, Sri; Putri, Eka Intan Kumala; Novindra, Novindra; Hastuty, Hastuty (Jurnal Ekonomi dan Pembangunan Indonesia, 2011)
This paper attempts to examine the impact of rising fossil fuel prices on the increasing impact on the demand of alternative fuels (biofuels), and its impact on food availability in Indonesia. An econometric model using simultaneous equations is employed. An increase in world crude oil price for 0,192 percent caused the price of real Indonesian palm oil export raised by 10,64 percent. Consequently, a larger biodiesel production is needed to meet their crease of world's consumer demand for biodiesel. Also, with the increase in real export price of Indonesian palm oil, it" will encourage palm oil producers to push their export volume. Indonesian palm oil exporter expected to increase by 6,37 percent to finally push the domestic CPO price increase for 1,85 percent. Rising domestic oil prices are causing oil demand in the palm oil industry to decline by 0,49 percent and in the end resulting in the decline of palm oil production by1,56 percent.